A new universal real flow of the Hilbert-cubical type. Issue 2 (3rd April 2019) - Jin, Lei; Tu, Siming
ABSTRACT: We provide a new universal real flow of the Hilbert-cubical type. We prove that any real flow can be equivariantly embedded in the translation onL ( R ) N, whereL ( R ) denotes the space of 1-Lipschitz functionsf : R → [ 0, 1 ] . Furthermore, all those functions inL ( R ) N that are images of such embeddings can be chosen asC 1 -functions.